The relationship between malocclusion and speech patterns: a cross-sectional study - Nada E. Tashkandi; Razan AlDosary; Hissah Zamandar; Misk Alalwan; Mohannad Alwothainani; Hissah Aljoaid; Duaa Alghazhmri; Eman Allam; Anand Marya; Samar M. Adel (BMC Oral Health)
Abstract Objective Dental occlusion and the alignment of the dentition play crucial roles in producing speech sounds. The Arabic language is specifically complex, with many varieties and geographically dependent dialects. This study investigated the relationship between malocclusion and speech abnormalities in the form of misarticulations of Arabic sounds. Materials and methods One hundred native subjects (28.92 ± 12.09 years old) were recruited for this cross-sectional study. The Peer Assessment Rating (PAR) index was used to describe malocclusion pattern. A standard speech sample was recorded for each subject and evaluated by a blinded speech therapist to judge misarticulations and indicate the misarticulation classification. The Jeddah Institute for Speech and Hearing Centre (JISH) articulation test was used to assess the phonologic abilities of the participants. Mann-Whitney U test was utilized for the statistical analysis. P-value < 0.05 was considered statistically significant. Results The PAR score ranged from 0 to 15, with an average of 4.87. The descriptive statistics of the included sample demonstrated that twenty-seven subjects showed improper articulation of sounds, with 25 being distortions and 2 substitutions. No significant gender differences were reported. A statistically significant association between PAR scores was recorded for the sounds / ص/ (p = 0.004), / ز/ (p = 0.017), and / س/ (p = 0.010). Conclusions There was an evident pattern of partial association of PAR index scores and speech abnormalities including improper articulation. To provide optimal care for involved subjects, collaboration between orthodontists and speech therapists, in pre- and post-treatment evaluations, is crucial.